Risk factors affecting the outcome of management of intertrochanteric fractures with dynamic hip screw in elderly patients: a retrospective, observational study - Bhosale, Nanasaheb D.; Naikwade, Deepak (International Journal of Research in Orthopaedics, 2023)
Background: Among the different fixation procedures for intertrochanteric fractures, dynamic hip screw fixation is the most used therapy. Present study evaluated the risk factors affecting the outcome of intertrochanteric fractures managed by dynamic hip screw fixation. Methods: This was an observational retrospective study conducted between March 2021 and February 2022. Patients with intertrochanteric fractures aged >60 years presenting within a week after incurring the fractures were enrolled. Evan’s and AO/OTA classification were used to categorize patients. “Failed” surgery was considered based on one of the following radiographic criteria. Functional outcomes were assessed at 6-months by Harris hip score (HHS). Results: 40 patients were enrolled, majority being females (n=22, 55%) with mean age of 67.79±4.76 years. Commonest mode of injury was fall while standing (n=32, 80%). Based on Evans classification, majority cases were stable fractures (n=25, 62.5%). By the AO/OTA classification, majority patients were under A2 class (n=22, 55%). The 30 cases (75%) had outstanding to good outcomes based on HHS assessment. 8 patients (20%) had “failed” surgical outcomes of which commonest presentations were >20 mm lag screw pull-out (n=4, 10%) and mal union (n=2, 5%). Mean age, and number of obese patients were found to be significantly greater in the “failed fracture” subgroup, versus “united fracture” subgroup (p<0.05). Significantly greater number of cases in “failed fracture” subgroup belonged to Evans’ class IV or V, and to A3 class of AO/OTA classification (p<0.05). Conclusions: Patient factors like greater age, obesity and intertrochanteric unstable fractures as indicated by Evans’ and AO/OTA classification were risk factors affecting the outcome of intertrochanteric fractures, managed with dynamic hip screw.